Scalable asynchronous domain decomposition solvers for non-homogeneous elastic structures. (December 2022) - Gbikpi-Benissan, Guillaume; Rynkovskaya, Marina; Magoulès, Frédéric
Abstract: This paper introduces a non-overlapping counterpart of the recently achieved two-level asynchronous restricted additive Schwarz (AsyncRAS) solver. It improves the asynchronous additive coarse-space correction therein designed and combines it with another recent asynchronous substructuring method by reformulating it under multisplitting iterative scheme, which makes it applicable to symmetric positive definite problems, as well established for a class of asynchronous multisplitting methods. Experimental performance and scaling results on an elastic helical structure with or without material reinforcement show the superiority of the proposed non-overlapping alternative to the two-level AsyncRAS. Highlights: Accurate non-blocking global residual calculation for effective asynchronous coarse-space correction. Multisplitting formulation of asynchronous substructuring methods. Better experimental performances regarding the state-of-the-art two-level asynchronous domain decomposition method. Practical scaling on a thin helical reinforced structure bending problem.